Falling asleep at the wheel and distracted driving. The High-Risk Professional Drivers study - Rosso, Gian Luca; Candura, Stefano; Perotto, Massimo; Caramella, Michele; Montomoli, Cristina (La Medicina del Lavoro, 2018)
Background: Sleepiness at the wheel and driving while engaged in other activities are well known risk factors for traffic accidents. This article estimates the prevalence of these factors among Italian Professional Drivers (PDs) and their impact on reported driving mistakes. Methods: A cross-sectional study was conducted using anonymous questionnaires. PDs (n=497) were divided into two groups: high-risk PDs (HiRis_PDs) (those who self-reported more than one incident during the last 3 years and/or more than one mistake during the past year) and non-HiRis_PDs (subjects who did not meet the above-mentioned inclusion criteria). Logistic regression analyses were performed to assess the association of self-reported sleepiness and/or risky driving behaviour with the condition of being a high-risk driver. Results: 161 (32.4%) subjects were defined as HiRis_PDs. Forty-one percent of the interviewees experienced at least one episode per month of sudden-onset sleep at the wheel. Twenty-eight point two percent reported a regular use of a hand-held cell phone. Predictive factors for being HiRis_PDs were: at least one self-reported episode per month of falling asleep at the wheel [odds ratio (OR) 5, 95% confidence interval (CI) 3.21-7.80, P<0.001], driving while regularly engaged in other activities (mainly hand-held cell phone use) (OR 6.11, 95% CI 2.90-12.84, P<0.001), and young age (OR 0.96, OR 1 year of age increase, 95% CI 0.94-0.98, P=0.001). Conclusions: Focusing prevention efforts on recognizing sleepiness at the wheel and on avoiding other distracting activities while driving can reduce the possibility of driving errors on the road by about 5-6 times.